50 years of Anderson localization - Abrahams, Elihu (International journal of modern physics : Condensed matter physics, statistical physics, applied physics, 2010)
This unique volume celebrates the five decades of the impact of Anderson localization on modern physics. In addition to the historical perspective on its origin, it provides a comprehensive description of the experimental and theoretical aspects of Anderson localization.